A task-based needs analysis for Australian Aboriginal students: Going beyond the target situation to address cultural issues - Oliver, Rhonda; Grote, E.; Rochecouste, J.; Exell, Michael (Australian Vocational Education and Training Research Association, 2013)
While needs analyses underpin the design of second language analytic syllabi, the methodologies undertaken are rarely examined. This paper explores the value of multiple data sources and collection methods for developing a needs analysis model to enable vocational education and training teachers to address the needs of Australian Aboriginal students from remote communities who speak Australian English as an additional language (EAL). Adopting a task-based approach to needs analysis, data were gathered from educators, students, potential employers and Aboriginal community members using interviews, observation and document collection. The findings highlight the benefits of a needs analysis for triangulating multiple data sources and methods to identify the actual target tasks, including social workplace interactions as well as cultural issues. These findings have implications for all language needs analyses, particularly for EAL students from non-Western cultures.